Wetland Ecological Models - H. Carl Fitz; N. Hughes (EDIS, 2008)
SL-257, a 6-page illustrated fact sheet by H.C. Fitz and N. Hughes, summarizes the types of ecological models that are used to better understand “natural” wetland ecology. Includes references. Published by the UF Department of Soil and Water Sciences, February 2008.